Journal Decision Support System in the Selection of Tourism Objects in Tulungagung Regency Using the Profile Matching Method - Fibriana, Arantika Dwi; Wurijanto, Tutut; Sukmaaji, Anjik (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
Tulungagung is one of regencies in East Java which has many various tourism object, from natural, historical, culinary, artificial, and shopping. Hence, the tourist should more selective in choosing tourism objects that suit their wants and needs. This tourism object selection is very important for travel convenience, so it does note cause problems for the tourist. In order to solve this problem, a Decision Support System for selecting a tourism object in Tulungagung was built. There are 5 criteria used: cost, distance, cleanliness, type of tourism, and facilities. In this research, the method that used is Profile Matching and this system was built on a web basis. The result of this research is that Decision Support System for choosing a tourism objects in Tulungagung can make tourist more easier for choosing tourism objects that suit their wants and needs.Â Keyword: Decision Support System, Tourism Object, Profile Matching